The danish way of parenting ebook What the happiest people in the world know about raising confident, capable kids. - Alexander, Jessica Joelle (2016)
International bestseller As seen in The Wall Street Journal —from free play to cozy together time, discover the parenting secrets of the happiest people in the world What makes Denmark the happiest country in the world—and how do Danish parents raise happy, confident, successful kids, year after year? This upbeat and practical book presents six essential principles, which spell out P-A-R-E-N-T: P lay is essential for development and well-being. A uthenticity fosters trust and an "inner compass." R eframing helps kids cope with setbacks and look on the bright side. E mpathy allows us to act with kindness toward others. N o ultimatums means no power struggles, lines in the sand, or resentment. T ogetherness is a way to celebrate family time, on special occasions and every day. The Danes call this hygge —and it's a fun, cozy way to foster closeness. Preparing meals together, playing favorite games, and sharing other family traditions are all hygge. (Cell phones, bickering, and complaining are not!) With illuminating examples and simple yet powerful advice, The Danish Way of Parenting will help parents from all walks of life raise the happiest, most well-adjusted kids in the world.